Evaluasi Penerapan Teknologi Keuangan (FINTECH) dalam Upaya Meningkatkan Pengelolaan Keuangan Koperasi Dan Manfaatnya bagi Anggota - Endang Wahyuningsih; Nurul Siti Sobariah (J-Coop : Journal of Co-operative, 2026)
The adoption of financial technology (fintech) has become a strategic approach for cooperatives to improve financial management effectiveness and enhance member services in the digital era. This study aims to evaluate the implementation of fintech in the Savings and Loan Unit of the Primkoppol Satbrimob Polda West Java Cooperative, assess its contribution to financial management and performance, and identify the benefits and challenges for members. The research employed a case study design with a descriptive quantitative approach. Data were collected through questionnaires and field observations, and the analysis was conducted to objectively assess the effectiveness of fintech implementation. The findings indicate that fintech adoption significantly improves transaction efficiency, enhances transparency in financial management, and increases accessibility to savings and loan services for members. Furthermore, digital financial systems support more accurate financial decision-making and improve member satisfaction. However, challenges remain, particularly related to limited digital literacy among some members and suboptimal technological infrastructure. The study concludes that fintech plays a significant role in strengthening cooperative financial management, with implications emphasizing the need to enhance digital literacy, improve human resource competencies, and develop robust digital security systems to ensure sustainable digital transformation within the cooperative sector.